The Effects of Conventional Physical Therapy with and Without Dry Needling on Pain, Range of Motions and Functional Disability in Patients with Shoulder Impingement Syndrome - Maqsood, Aqsa; Asim Arif, Muhammad; Ijaz Ahmed Burq, Hafiz Syed; Jawa, Rabia; Rizwan, Muhammad; Amin, Tooba (Pakistan BioMedical Journal, 2022)
Dry needling is a technique in which thin monofilament-based needles are inserted into soft tissues, especially trigger points in muscles. It is being used in a range of neuromuscular pain syndromes such as shoulder impingement syndrome in current study. In physical therapy, it is narrowly referred to as an intramuscular procedure for the treatment of myofascial trigger points (MTrPs). Objective: To compare the conventional physical therapy with and without dry needling on pain, range of motion, and functional disability in patients with shoulder impingement syndrome. Methods: It was randomized controlled trial conducted on 66 patients of shoulder impingement syndrome based on inclusion criteria and divided randomly allocated equally in two groups of 33 in each of conventional therapy and dry needling group. The outcome measures used were numeric pain rating scale for pain, DASH for hand arm function and shoulder ranges of motion. The SPSS 25.0 was used to analyse data. The descriptive statistics was applied, and inferential statistics was applied based on findings of tests of normality. Results: The results showed that the post interventional pain score was 1.43±1.37, 32.11 for conventional group and for experimental group that of 1.60±1.02, 34.89 with non-significant difference 0.544, while DASH score was 27.02±13.22, 38.85 for conventional group and for experimental group that of 19.92±11.20, 28.15 with significant difference 0.024. The results for flexion, abduction, internal and external rotation were non-significant with p value >0.05. Conclusions: It was concluded that although there was significant improvement in pain, range of motion and function in both of dry needling and conventional groups, however, pain and shoulder ranges improved equally in both groups without a statistically significant difference while that of disability improved significantly in dry needling group